Measuring Green Supply-Chain Performance Using the Green SCOR Approach at the IKM Gallery of Malang Regency - Sunday Noya; Luigi Takaria (Jurnal Rekayasa Sistem & Industri, 2022)
Measurable supply chain management is a method to improve supply chain performance in Small andMedium Industries (IKM). This research was conducted through field observations to discover theproblems of the supply chain system in the IKM Gallery Kab. Malang. Using the Green SCORmeasurement concept, Key Performance Indicators (KPI) are determined which will be used as the basisfor measuring supply chain performance. The three main components in the IKM Gallery used asmeasurement indicators are (1) Deliver, consisting of Deliver Quantity Accuracy, Shipping DocumentAccuracy, and Deliver Cycle Time; (2) Return, consisting of Percent of Complaint Regarding MissingEnvironmental Requirements from Product and Percent of Error-Free Return Ship; and (3) Enable,consisting of Percent of Employee Educated in Environmental Requirements. KPI is used to calculate theSNORM normalization value which indicates the performance level. The calculation results show that thefinal performance value of all components is 79.16 which is classified in the "Good" category.